Kampanye Sadar Tuberkulosis (TB) Berbasis Health Education di Nagari Punggung Kasiak - Linda Marni; Armaita Armaita; Rika Armalini (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, is a disease that is strongly influenced by environmental factors and has infected approximately one-third of the world’s population. Padang Pariaman Regency is the area with the second-highest incidence of TB in West Sumatra Province. Based on interviews conducted at the Lubuk Alung Public Health Center, since 2017 Nagari Punggung Kasiak has tended to have a high proportion of TB suspects, with an average rate of more than 35%. This finding indicates that many community members are unaware that they have been infected with TB, even though TB is a highly transmissible disease, and mortality due to TB is higher than that caused by malaria and AIDS. The problems in Nagari Punggung Kasiak are mainly related to unhealthy environmental conditions and a lack of community concern when family members or neighbors experience a persistent cough that may indicate TB. Therefore, a solution was implemented by promoting a healthy environment through health education. The health education provided differed from conventional approaches, namely by developing various tuberculosis-related attributes and conducting campaigns both digitally and through direct visits to community households. This campaign was carried out in collaboration with the nagari government, 13 selected community health volunteers appointed as TB cadres, and representatives from the public health center, who jointly disseminated tuberculosis-related attributes. Through this campaign, it was expected that the community would feel comfortable discussing TB with the team, thereby increasing public knowledge about tuberculosis. The mandatory outputs of this activity included a video documentation of the activities, publications in the local media Khaz Ranah, and publication in a health journal (SINTA 4). Additional outputs included improvements in community health conditions, reflected in a shift from low awareness to a community that is alert and responsive to TB.